AN INVESTIGATION INTO THE SCHOOL INFASTRUCTURE AND PREPAREDNESS IN IMPLEMETING THE PROPOSED GOVERNMENT TABLET PROJECT FOR STANDARD ONE PUPIL’S : A CASE STUDY OF KINANGOP SUB -COUNTY, NYANDARUA COUNTY, KENYA - Kahungu, Peris Gathoni; Kibaara, Tarsilla M.; Marete, Jacob Bundi (IJRDO- Journal of Educational Research, 2017)
The Government, in 2013, proposed to implement a tablet project for ICT integration ineducation so as to improve the quality of education in Kenya. The study therefore sought toestablish the viability of this project by looking into whether teachers had the necessary ICTskills and the availability of the necessary infrastructure. The study concluded that primaryschools in the Sub-County had adequate storage facilities. It was also established that allschools within are connected to mains electricity and the study concluded that the internetconnectivity was poor in over half the schools. The study also noted that teachers in primaryschools had ICT skills but there is need to further train teachers to enhance teaching andlearning, and to raise education standards. The lack of ICT skills, time and disinterest in ICTneeds to be addressed to improve the perception and attitudes of teachers towards ICT use